Slang Expressions in Big Hero 6 Movie - Laksono, Aditya Bimo; Maharini, Sang Ayu Isnu; Sukarini, Ni Wayan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research entitled “Slang Expressions in Big Hero 6 Movie” focuses on identifying the types and functions of slang in the movie. This research applied documentation method to collect the data completed with note-taking technique. The data were taken by watching the movie and taking notes of the slang expressions found in the movie. In analysing the data, qualitative method is applied and the findings are presented descriptively. The findings reveal the presence of 22 expressions in fresh and creative, flippant, imitative, and clipping types. The slang types and their functions are categorized according to Allan and Burridge’s theory with supporting theory by Halliday.